Business Process Simulation Game as a Business Process Learning Tool for Retail Companies - Joella Joella; Yulia Yulia; Andreas Handojo (Institute of Research and Community Outreach - Petra Christian University, 2021)
Game-based Learning has become one of the most developed learning methods in this 21st century. Game-based Learning is a good learning method because it can create a virtual world where players can simulate real-world problem-solving. A business process is a series of interrelated activities to achieve certain business goals, executed sequentially or parallel, both inside and outside the company. The complexity of business processes causes the learning process to be less than optimal, if only in the form of theoretical exposure. Practices are needed to hone students’ business process management skills, which will be too risky to be done in the real world. Therefore, this research develops a business process simulation game to facilitate students in practicing their business process management skills. The author analyzed the existing business process simulation games, determined the game system design, developed the game, tested the game, and distributed questionnaires to users. Based on the results of testing and implementing the system that has been done, the game developed in this research has a positive impact on users. The features in the game are running well and as expected. The game provides benefits to both teachers and students, so this game is suitable for being used as retail companies' business process learning tool